2008
DOI: 10.1007/s00468-008-0284-x
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthetic capacity and temperature responses of photosynthesis of rubber trees (Hevea brasiliensis Müll. Arg.) acclimate to changes in ambient temperatures

Abstract: The aim of this study was to assess the temperature response of photosynthesis in rubber trees (Hevea brasiliensis Müll. Arg.) to provide data for process-based growth modeling, and to test whether photosynthetic capacity and temperature response of photosynthesis acclimates to changes in ambient temperature. Net CO 2 assimilation rate (A) was measured in rubber saplings grown in a nursery or in growth chambers at 18 and 28°C. The temperature response of A was measured from 9 to 45°C and the data were fitted t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
50
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(56 citation statements)
references
References 48 publications
5
50
0
1
Order By: Relevance
“…In addition, P-Ti showed lower at 14/14 °C regime compared to other regimes. Our results agreed with the findings of Kositsup et al (2009) andulqodry et al (2014) that P-Ti decreased at a low and high leaf temperatures, and showed lower at a low-growth temperature regime compared with at higher growth temperature regimes.…”
Section: Effects Of Contrasting Temperature On Leaf Constituentssupporting
confidence: 83%
“…In addition, P-Ti showed lower at 14/14 °C regime compared to other regimes. Our results agreed with the findings of Kositsup et al (2009) andulqodry et al (2014) that P-Ti decreased at a low and high leaf temperatures, and showed lower at a low-growth temperature regime compared with at higher growth temperature regimes.…”
Section: Effects Of Contrasting Temperature On Leaf Constituentssupporting
confidence: 83%
“…The temperature sensitivities of both photosynthesis and respiration can change, and there are ecophysiological arguments that plants can acclimate to a warming of a few degrees [59,60]. However, there are very few empirical data on the degree to which tropical trees respond and are able to acclimate to increased temperatures and drought [61][62][63]. Several contemporary dynamic vegetation models may be overly sensitive to temperature and not allowing for acclimation effects [31].…”
Section: Discussionmentioning
confidence: 99%
“…The differences might be closely related to the highly diverse environmental conditions in which plants grown. CO 2 and temperature are considered two of the primary environmental factors that determine, directly or indirectly, the photosynthetic capacity (Bunce, 2008;Stojanovic, 2008;Kositsup et al, 2009;Possell and Hewitt, 2009). Changes in CO 2 and temperature affect the photosynthetic capacity at the levels of leaf biochemistry, stomata and CO 2 diffusion as well as photosynthetic component activities and CO 2 partial pressure at the carboxylation sites.…”
Section: Introductionmentioning
confidence: 99%